TECHNO-EPISTEMOLOGY IN CONTEMPORARY PHILOSOPHY OF SCIENCE: CONCEPTUAL FOUNDATIONS FOR THE ANALYSIS OF NEW MEDIA - Sliusar, Vadym (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
Introduction. The digital era is marked by radical transformations in the means of knowledge production and dissemination, driven by the pervasive application of digital platforms, algorithmic systems, and artificial intelligence technologies. In this context, new media emerge as large-scale databases where information is generated and processed in real time for entire populations rather than selected samples. These shifts alter the very architecture of knowledge, creating a hybrid informational environment in which traditional criteria of truth and justification become increasingly ineffective. These transformations are directly related to the broader questions addressed in contemporary philosophy of data and information concerning the ontological status of data and the conditions for their conversion into knowledge under digitalization. The aim and tasks. The aim of the article is to substantiate techno-epistemology as a conceptual framework for the philosophical analysis of new media under conditions of digital transformation. The tasks are: to clarify the content of the concept of «techno-epistemology» and its theoretical origins in the philosophy of technology and philosophy of science; to systematize leading approaches to technological knowledge – from Carl Mitcham’s fourfold typology to Ori Freiman’s concept of techno-trust and Marek Hetmański’s technologised epistemology; to determine the specific role of new media as constitutive factors of cognitive processes; and to analyse algorithmic selection, platformisation of content, and cyclic knowledge order as defining features of the contemporary media environment. Research methods. The study employs comparative analysis of competing epistemological concepts and an interdisciplinary synthesis drawing on philosophy of science, philosophy of technology, media studies, and social epistemology. Research results. Techno-epistemology is established as an independent direction within contemporary philosophy of science that integrates individual, social, and technological dimensions of cognition, replacing the classical justification–truth–belief triad. Technological knowledge is distinguished from scientific knowledge by a normative component evaluated not by truth but by effectiveness. New media are shown to function as constitutive factors of cognitive processes that construct, rather than reflect, media reality through algorithmic selection, personalised news feeds, and generated content. The connection between techno-epistemological analysis of new media and the philosophy of data and information is outlined as a productive direction for further research. Conclusions. Techno-epistemology is establishing itself as an independent branch of contemporary philosophy of science, integrating the individual, social, and technological dimensions of cognition, while new media act not as neutral channels but as agents in the construction of knowledge through algorithmic and platform-based mechanisms. At the same time, digital transformation drives a shift toward a process-oriented, open nature of knowledge and necessitates the development of new methodological approaches to analysing the interaction between technologies, media, and audiences, where techno-epistemology can perform a reflective function.